The fatty acid composition of serum phospholipids in adolescents is associated with body composition in early adulthoods: an eight-year follow-up study - Metelcová, T; Zamrazilová, H; Vaňková, M; Hill, M; Tvrzická, E; Staňková, B; Taxová Braunerová, R; Hainer, V; Kunešová, M (Physiological research, 2022)
The fatty acid composition is associated with obesity. Omega 3 polyunsaturated fatty acid (PUFA) could have a beneficial role in the prevention and treatment of many disorders, including cardiometabolic diseases. A cohort of 84 men and 131 women were examined in adolescence and after 8 years. Body weight (BW) and fat mass (FM) were measured. The composition of fatty acids (FAs) of serum phospholipids was assessed using gas chromatography. Statistics: PLS method. Aim: to determine the relationships between FAs in adolescence and FM (explanatory variable 1, EV1) and BW (explanatory variable 2, EV2) in adulthood. In the predictive models, a cluster of FAs in boys explained 47.2 % of EV1 and a cluster of 6 FAs in girls explained 32.3 % of EV1 measured in adulthood. FAs measured in adolescents explained 23.7 % of EV2 in early adults regardless of gender. A significant negative association was found between 18:1n-9c and EV1 in males and EV2 in both genders. We found a significant negative association between 18:2n-6 and 20:0 and both EV1 and EV2. In all analyses, we found a significant negative association of 20:1n-9 and 18:3n-3 with EV1-2 in both genders. A significant positive association was found in 20:3n-6 with EV1 and EV2 in males. 20:4n-6 was positively associated with EV1 in females and EV2 in both genders. A positive association between FM and very long chain n- 6 PUFAs was also observed. It is concluded that serum MUFAs and essential PUFAs in adolescence are associated with lower BW and FM in adulthood.
Keywords: dospělí; Fatty Acids, Omega-3; mastné kyseliny; Female; Adult; Fatty Acids; ženské pohlaví; Adolescent; lidé; fosfolipidy; následné studie; Fatty Acids, Unsaturated; omega-3 mastné kyseliny; tělesná hmotnost; Follow-Up Studies; Male; složení těla; nenasycené mastné kyseliny; Phospholipids; Body Weight; Body Composition; mužské pohlaví; mladiství; Humans